Szervezési és ökonómiai kérdések a régiós kertészeti termékek előállításában - Ferencz, Árpád; Nótári, Márta (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
In my work I evaluate the work organization and economy of a hungaricum cherry orc-hard. I studied the machine-, hand-, and mixed harvesting technologies. I wanted to know which of the three technological variables gives the best economic result in cherry grow-ing. In doing so I determined the technological and harvest costs. I study the income and profit of each harvest type. Using economic indexes I point out the most optimal harvest type which gives the highest profit for the enterprise. In my work I also wish to know whether a „clear" one-type harvest can meet the above requirements.